Comparison of Auditory and Visual Oddball fMRI in Schizophrenia - Collier, Azurii K. (Schizophr Res, 2014)
Individuals with schizophrenia often suffer from attentional deficits, both in focusing on task-relevant targets and inhibiting responses to distractors. Schizophrenia also has a differential impact on attention depending on modality: auditory or visual. However, it remains unclear how abnormal activation of attentional circuitry differs between auditory and visual modalities, as these two modalities have not been directly compared in the same individuals with schizophrenia. We utilized event-related functional magnetic resonance imaging (fMRI) to compare patterns of brain activation during an auditory and visual oddball task in order to identify modality-specific attentional impairment. Healthy controls (n = 22) and patients with schizophrenia (n = 20) completed auditory and visual oddball tasks in separate sessions. For responses to targets, the auditory modality yielded greater activation than the visual modality (A-V) in auditory cortex, insula, and parietal operculum, but visual activation was greater than auditory (V-A) in visual cortex. For responses to novels, A-V differences were found in auditory cortex, insula, and supramarginal gyrus; and V-A differences in the visual cortex, inferior temporal gyrus, and superior parietal lobule. Group differences in modality-specific activation were found only for novel stimuli; controls showed larger A-V differences than patients in prefrontal cortex and the putamen. Furthermore, for patients, greater severity of negative symptoms was associated with greater divergence of A-V novel activation in the visual cortex. Our results demonstrate that patients have more pronounced activation abnormalities in auditory compared to visual attention, and link modality specific abnormalities to negative symptom severity.